(untitled) (Revista Archai, 2018)
The aim of this paper is to verify how the problem of knowledge is developed in Foucault’s readings of the tragedy, Oedipus the King. Between the discovery of himself and the revelation of truth that liberates Thebes, it happens in Oedipus the passage from ignorance to knowledge, which delimits, throughout the entire play, a complex game of knowledge: listening and vision knowledge; distance and presence knowledge; kings knowledge and the slave hut background knowledge; prediction and testimony knowledge; knowledge that voluntarily withdraws from the enigma and knowledge that lurks beneath the fear and only the threat can extract it. For Foucault, Oedipus holds an excess knowledge which determines his character, his mode of action and destiny.